Who keeps smoking? A repeated cross-sectional analysis of adolescent behaviour in Indonesia - Ardhianto, Widiawan Sukarno; Hartono, Hartono; Widyaningsih, Vitri; Mulyaningsih, Tri (Edelweiss Applied Science and Technology, 2025)
Adolescent smoking remains a significant public health issue, particularly in low- and middle-income countries such as Indonesia. This study examined how socio-demographic, economic, environmental, and psychological factors influence smoking initiation and persistence among adolescents. A repeated cross-sectional analysis was conducted using data from the Indonesian Family Life Survey (IFLS) waves 3 (2000), 4 (2007), and 5 (2014), focusing on adolescents aged 15–19 years. Smoking initiation was defined as having ever smoked, and persistence as continued smoking after initiation. Logistic regression was used to assess associations with age, gender, education, academic performance, parental smoking, income, school characteristics, area of residence, and depressive symptoms. Results showed that while overall initiation declined, older adolescents (17–19 years), males, and those from low-income households remained at higher risk. Being employed increased the odds of initiation, while higher education was protective. Persistence was more likely among males, unemployed adolescents, and those with smoking parents. Depression was associated with increased initiation but lower persistence, suggesting experimentation rather than long-term use. These findings highlight the roles of socioeconomic and mental health factors in shaping smoking behavior. Targeted tobacco control interventions and integrated mental health support are urgently needed, particularly for male adolescents and those exposed to parental smoking.